(untitled) (Acta Scientiarum. Agronomy, 2014)
Jatropha curcas has a high biofuel oil content, which could replace polluting fuels, and has great potential for large scale monoculture cultivation in the conventional system. We explored the occurrence, spatial distribution and the functional response of the main phytophagous species of this plant and their natural enemies to explore the potential for conservative biological control. We began sampling phytophagous species and predators when J. curcas plants were six months old. The most common species of phytophagous insects were nymphs and adults of Empoasca kraemeri, followed by Frankliniella schultzei and Myzus persicae. Among the predators, Ricoseius loxocheles, Iphiseioides zuluagai, Araneidae, larvae and adults of Psyllobora vigintimaculata and Anthicus sp. were the most frequently encountered. The most common parasitoids were the families Encyrtidae and Braconidae. The highest densities of E. kraemeri and F. schultzei on the edges of the J. curcas crop follow spatial patterns similar to those of their natural enemies I. zuluagai and Anthicus sp. These arthropods can be considered efficient predators of immature stages of E. kraemeri and F. schultzei on J. curcas.